PROFIL VEGETASI PEKARANGAN DI DESA JABON MEKAR, KECAMATAN PARUNG, BOGOR - Budi Prasetyo (Jurnal Matematika Sains dan Teknologi, 2007)
Jabon Mekar village is well-known by people as the central of fruit producing at subdistrict of Parung. However it was estimated as a buffer zone of Jakarta and subject of the urban development. The aim of the research is to study the vegetation profile and the tree of model architecture at home-garden of community in the village of Jabon Mekar. The methods used for vegetation analysis were the quadrate method and the vegetation profile architecture method. The result of the vegetation profile at home-garden research shows that according to their formation of canopy coat, there were five stratums. Based on the vertical and horizontal of profile diagram, the dominant species of plants is Gnetum gnemon, with Fagerlind model of architecture; and the co-dominant species of plants is Musa sp., with Tomlinson model of architecture. The domination of these two trees of architecture models will give a limited chance of having an erotion process at the home-garden society.